Perylene-embedded electrospun PS fibers for white light generation. (January 2019) - Guner, Tugrul; Aksoy, Erkan; Demir, Mustafa M.; Varlikli, Canan
Abstract: Perylene dyes have been employed in the fabrication of white light due to their superior photophysical properties and relatively easy synthetic methods. However, their molecular aggregation in solid state is one of the main handicaps since it causes deviation in their optical properties and quenches photoluminescence quantum yields (Φf ). Investigation of the photophysical properties of a green (PTE), a yellow (PDI) and a new red (DiPhAPDI) emitting perylene derivative in solution, drop-casted films, polystyrene (PS) fibers and PS fibers embedded in poly (dimethyl siloxane) (PDMS) showed that PS:dye fibers prevent aggregation to some extend and allows high Φf of dyes. The Φf values of PTE, PDI and DiPhAPDI were all higher than 93.0% in solution and 84.8%, 94.3% and 73.6%, respectively in PS:dye fibers. Embedding the fibers in PDMS improved the photostabilities of the dyes two folds compared to their solution phases. The prepared dye containing fibers were combined together into a single PDMS film and utilized as a frequency conversion layer on a blue LED. Fabricated samples were found to show high color rendering index (≥90), adjustable CCT (7500 K–5000 K), and power efficiency values exceeding 200 l m/W depending on the used fiber amount in mass. Graphical abstract: Image 1 Highlights: Green, yellow and red emitting perylene dyes were synthesized. High photoluminescence quantum yields were obtained in polystyrene fibers. Embedding the fibers in PDMS improved the photostabilities of the dyes two folds. Dyes were utilized as frequency converters to generate white light. High CRI, adjustable CCT and high PE values were obtained.